Methods and Strategies for Reconditioning Motor Output and Postural Balance in Frail Older Subjects Prone to Falls - Paillard, Thierry (Frontiers in Physiology, 2021)
In frail older subjects, the motor output of the antigravity muscles is fundamental in resisting falls. These muscles undergo accelerated involutions when they are inactive and the risk of falling increases during leisure and domestic physical activity. In order to reduce their risk of falling, frail older subjects limit their physical activities/exercises. The problem is that the less they exercise, the less they are able to exercise and the greater the risk in exercising. Hence, a vicious circle sets up and the antigravity muscles inevitably continue to deteriorate. This vicious circle must be broken by starting a reconditioning program based on developing the strength of antigravity muscles (especially lower-limb muscles). To begin with, for each increase in muscle strength, postural balance is improved. Once this increase reaches the threshold beyond which postural balance no longer improves, it seems appropriate to implement exercises aimed at concomitantly improving motor output and postural balance in order to counteract or even reverse the involution process of the postural balance system. Methods and strategies towards this end are proposed in this present communication. However, the transfer effects between strength increase and postural balance ability are not yet totally known and future research should study them for each physiological profile in all older subjects (frail or not).